Ingvild Sælid Gilhus, Siv Éllen Kraft and James R. Lewis, New Age in Norway. (25th January 2019) - Lutkajtis, Anna
Abstract : Ingvild Sælid Gilhus, Siv Éllen Kraft and James R. Lewis, New Age in Norway. Sheffield, UK and Bristol, CT: Equinox, 2017, pp. xiv + 290, ISBN: 978-1-78179 417-3 (pbk).